Curcumin induces tumor suppression in ameloblastoma by promoting apoptotic mechanism via MiR-9 expression: A narrative review - Hanif, Hilmy Irsyadi; Hardiyani, Reisca Tiara; Septiani, Intan Dzahabiyah; Susilowati, Heni (Indonesian Journal of Dental Medicine, 2024)
Background: Ameloblastoma is a neoplastic odontogenic tumor that has a local invasive characteristic. The current treatment for ameloblastoma requires a precise surgical resection and chemotherapy. It requires a different approach to diminish the therapy drawbacks. Curcumin, as one of the most common well-described compounds, remarkably has a potential antitumor agent. Method: Our findings and opinions are based on a comprehensive search through scientific resources and correspondingly relating all the keywords using the Boolean technique and Medical Subject Headings (MeSH) term search to find the interest study. Review: By understanding curcumin and its target genes, curcumin itself can induce regulation of tumor suppression and oncogenic microRNA. MiR-9 has proven to be expressed for modulating the mutation genes causing tumorogenesis in ameloblastoma. Curcumin also upregulates miR-9, causing cytotoxic activity against cancers in many proven studies. Conclusion: The highly expressed miR-9 curcumin-mediated ameloblastoma inhibition will be the new insight and adjunct cancer therapy.